Blue Light Improves Vase Life of Carnation Cut Flowers Through Its Effect on the Antioxidant Defense System - Aalifar, Mostafa; Aliniaeifard, Sasan; Arab, Mostafa; Zare Mehrjerdi, Mahboobeh; Dianati Daylami, Shirin; Serek, Margrethe; Woltering, Ernst; Li, Tao (Frontiers in Plant Science, 2020)
Postharvest senescence is the common concern for development of cut flower industry. Improving marketability and extension of vase life of cut flowers have a great practical significance for this development. Although considerable efforts have been made during the last few decades to improve the vase life of cut flowers through controlling the environmental cues and through the use of floral preservatives during postharvest storage, the impact of lighting environment on the vase life is largely overlooked. In the current study, the effect of three LED light spectra [white (400-730 nm), blue (peak at 460 nm) and red (peak at 660 nm)] at 150 photosynthetic photon flux density (PPFD) on the vase life and on physiological and biochemical characteristics of carnation cut flowers was investigated. Exposure to blue light (BL) considerably delayed senescence and improved the vase life over flowers exposed to red light (RL) and white light (WL). H2O2 and malondialdehyde (MDA) contents in petals gradually increased during the vase life; the increases were lowest in BL-exposed flowers. As a consequence, BL-exposed flowers maintained higher membrane stability index (MSI) compared to RL- and WL-exposed flowers. A higher activity of antioxidant enzymes [superoxide dismutase (SOD), peroxidase (POD), catalase (CAT) and ascorbate peroxidase (APX)] was detected in petals of BL-exposed flowers, compared to their activities in RL and WL-exposed flowers. In BL-exposed flowers, the decline in petal carotenoid contents was delayed in comparison to RL- and WL-exposed flowers. Maximum quantum efficiency of photosystem II (Fv/Fm) and a higher percentage of open stomata were observed in leaves of BL-exposed flowers. Sucrose and glucose contents accumulated in petals during the vase life; sugar concentrations were higher in BL-exposed flowers than in RL and WL-exposed flowers. It is concluded that BL exposure improves the vase life of carnation cut flowers through its effect on the antioxidant defense system in petals and on photosynthetic performance in the leaves.